The Role of Educational Institutions in Promoting Community Security from the Point of View of the Teaching Staff at Schools and Universities in Amman - Zainelabdeen, Fatima Abdelhadi; Aladwan, Shadia Hasan; Alshamaileh, Nisreen (Dirasat: Educational Sciences, 2020)
The study aims to identify the role of educational and learning institutions in enhancing community security from faculty members’ perspectives. The study sample was selected using a stratified sampling method from faculty members at public and private schools at Amman city, Second Education Directorate, including members of the teaching staff at private and public universities in Jordan which consisted of (200) member. The study showed that school’s role in promoting community security came at a mid-high level, and the university’s role in promoting community security came at mid-high level from faculty members’ perspectives. The findings of the study showed a statistical signifigance level at (a = 0.05) between universitiy and school roles in enhancing community security and students’ commitment to applying security concepts on real life situations. The study recommends the necessity of conducting a similar study in different context (at the level of other governorates) in the Hashemite Kingdom of Jordan and comparing its results with this study. It also suggests the need to establish of security councils in schools and universities, which would increase the level of dialogue and openness in schools and universities . The study also recommends adding new curricula in schools and universities that discusses the concepts of human rights, and the culture of tolerance, dialogue and acceptance of others.